Numerical Modelling of Adiabatic Shear Bad Formation in a Twisting Test - Glema, A.; Kąkol, W.; Łodygowski, T. (Engineering Transactions, 1997)
The objective of the paper is the investigation of adiabatic shear band localized fracture phenomenon in a tubular specimen during dynamic loading processes. The fracture occurs as a result of an adiabatic shear band localization attributed to a plastic instability implied by thermal softening during dynamic plastic flow. The formulation of the physical problem is adopted following the paper by T. ŁODYGOWSKI and P. PERZYNA [8]. For regularized elasto-viscoplastic model, the numerical investigation of the three-dimensional dynamic adiabatic deformation in a particular body at nominal strain rates ranging from 103 to 104 s- 1 is presented. The attention is focussed on the discussion, which finite element models are acceptable for computational simulation of the real experiments, taking into account both the physical point of view and the computational efficiency. The restrictions in the creation of arbitrary 3-D models are discussed and for the case under consideration, a 2-D shell model is proposed. The results of computations (plastic strains and temperature rise) obtained in the environment of ABAQUS package [1] confirm the laboratory observations with satisfying accuracy.